Efek paparan Mikotoksin terhadap aktivitas Enzim Katalase pada hati ayam kampung di Desa Klitih - Zain, Muhammad Azka Shafara (Maliki Interdisciplinary Journal, 2024)
Storage of food ingredients that are not in accordance with sanitation and hygiene standards causes the growth of mold fungi accompanied by the release of mycotoxins. Food ingredients contaminated with mycotoxins if consumed by living creatures will be very dangerous because these substances are toxic. This research is descriptive in nature to analyze the impact of mycotoxin exposure on the liver of free-range chickens in Klitih village by looking at the observed data. External observations of the chicken’s body were carried out by routine inspection every day for one week. Observations regarding the effects that occur in the chicken’s body were carried out by reacting the chicken’s liver with hydrogen peroxide. The results and observational data stated that the native chicken used as the dependent variable was contaminated with aflatoxin B1 mycotoxin. This is evidenced by a significant reduction in chicken weight and liver function. This kind of incident can be prevented by improving the chicken housing system and providing food intake that meets health standards.